An Adult Tracheocele with No Predisposing Factor - Ertas, Burak; Ulug, Tuncay; Aydin, Kubilay (AVES, 2017)
Tracheoceles are rare, and usually, they have been described as incidental findings while evaluating patients for other problems. Our patient complained of a mass located in the right supraclavicular region that got larger on coughing and straining

otherwise, he was asymptomatic. His history did not reveal any predisposing factors. Computed tomography showed an air-filled 3x2.5x2 cm mass at the level of the T2-4 vertebrae. Surgical exploration showed an air-filled mass located between the common carotid artery and trachea, communicating with the tracheal lumen via a narrow tract attached to the posterior wall of the trachea. The mass was completely resected, and the defect in the posterior wall was repaired. A literature search revealed only one tracheocele case without any predisposing factors, and our case is a new one. It is different from other tracheocele reports considering the origin side, type, and level of the lesion.
Keywords: Tracheocele; diverticulum; neck; swelling